A writer's America landscape in literature - Kazin, Alfred 1915-1998 (Knopf, 1988)
Examines the American landscape, wild, pastoral, or urbanized, and its influence on poets, essayists, and novelists.
Keywords: Geschichte; Couleur locale dans la littérature; Littérature américaine - Histoire et critique; Nature dans la littérature; Paysage dans la littérature; États-Unis dans la littérature; American literature -- History and criticism; Landscapes in literature; Local color in literature; Nature in literature; Literatur; Landschaft -- Motiv; Lokalkolorit; USA; United States -- In literature